2018
DOI: 10.1002/ptr.6259
|View full text |Cite
|
Sign up to set email alerts
|

The novel protective effects of loganin against 1‐methyl‐4‐phenylpyridinium‐induced neurotoxicity: Enhancement of neurotrophic signaling, activation of IGF‐1R/GLP‐1R, and inhibition of RhoA/ROCK pathway

Abstract: Loganin, a major iridoid glycoside obtained from fruits of Cornus officinalis, possesses anti‐inflammatory, antitumor, antidiabetic, and osteoporosis prevention effects. Loganin has been linked to neuroprotection in several models of neurodegeneration, including Parkinson's disease (PD). However, mechanisms underlying the neuroprotective effects of loganin are still mostly unknown. Here, we demonstrated the protective effects of loganin against PD mimetic toxin 1‐methyl‐4‐phenylpyridinium (MPP+) and the import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…This extract was able to decrease the burden of oxidative stress and protect from the decline in cortical dopamine (DA), norepinephrine (NE), and serotonin (5‐hydroxytriptamine, 5‐HT) levels induced by amyloid β‐peptide, in rat cortex synaptosomes (Ferrante et al, ). Intriguingly, the multitarget mechanisms showed by both devil's claw extracts and harpagoside corroborate recent in vitro studies regarding the neuroprotective effects induced by iridoid compounds such as loganin and genipin (Liu, Chen, Lu, Fang, & Yu, ; Tseng, Lin, Chang, & Lo, ), thus supporting future in vivo investigations in order to confirm the efficacy and safety in the management of neurodegenerative diseases.…”
Section: Experimental Studiessupporting
confidence: 81%
“…This extract was able to decrease the burden of oxidative stress and protect from the decline in cortical dopamine (DA), norepinephrine (NE), and serotonin (5‐hydroxytriptamine, 5‐HT) levels induced by amyloid β‐peptide, in rat cortex synaptosomes (Ferrante et al, ). Intriguingly, the multitarget mechanisms showed by both devil's claw extracts and harpagoside corroborate recent in vitro studies regarding the neuroprotective effects induced by iridoid compounds such as loganin and genipin (Liu, Chen, Lu, Fang, & Yu, ; Tseng, Lin, Chang, & Lo, ), thus supporting future in vivo investigations in order to confirm the efficacy and safety in the management of neurodegenerative diseases.…”
Section: Experimental Studiessupporting
confidence: 81%
“…It is worth noting that the total content of compounds in the flowers was much higher than that in the other parts, especially that of iridoids, which was three times higher in the flowers than in the medicinal part (i.e., the roots). Modern pharmacological studies have shown that iridoids have antitumoral [28], hepatoprotective [29], neuroprotective [30], and other biological effects [6,31]. Therefore, S. ningpoensis flowers might provide a supplementary source of iridoids, be used as a source for the extraction of important bioactive compounds, and reduce the waste of nonmedical parts and environmental pollution.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the presence of IGF-1R antagonists (AG1024) or GLP-1R antagonists (exendin 9-39) weakened the protective effect of loganin on MPP+ -induced cytotoxicity and apoptosis, and decreased neuron length and ROS production. A series of experiments showed that loganin could enhance neurotrophic signals, activate IGF-1R/GLP-1R, inhibit RhoA/ROCK pathway, and alleviate MPP+ induced apoptosis and death, neuron damage, oxidative stress, and other mechanisms to achieve neuroprotective effect [53].…”
Section: Neuroprotective Effectsmentioning
confidence: 99%